Uncovering the Effect and Mechanism of Rhizoma Corydalis on Myocardial Infarction Through an Integrated Network Pharmacology Approach and Experimental Verification - Li, Jingyan; Wu, Junxuan; Huang, Junying; Cheng, Yuanyuan; Wang, Dawei; Liu, Zhongqiu (Frontiers in Pharmacology, 2022)
Background: Myocardial infarction (MI), characterized by reduced blood flow to the heart, is a coronary artery disorder with the highest morbidity and mortality of cardiovascular diseases. Consequently, identifying effective drugs to treat MI is urgently needed. Rhizoma Corydalis (RC) is the dry tuber of Corydalis yanhusuo W.T. Wang, and it is extensively applied for treating MI clinically in China, but its underlying pharmacological mechanism remains unknown. This study aimed to clarify the molecular mechanism of RC on MI by utilizing network pharmacology and experimental verification. Methods: Based on network pharmacology, the potential targets of the RC ingredients and MI-related targets were collected from the databases. Furthermore, core targets of RC on MI were identified by protein-protein interaction (PPI) network and analyzed by Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Molecular docking was used to validate the binding affinity between the core targets and the bioactive components. Oxygen-glucose deprivation (OGD) was performed on H9c2 cells to mimic MI in vitro. A Cell Counting Kit-8 assay was used to assess the cardioprotective effect of active ingredient against OGD. Western blot analysis and qRT-PCR was conducted to measure the cell apoptosis and inflammation level of H9c2 cells. Results: The network pharmacology results manifested that in all 60 bioactive components of RC with 431 potential targets and 1131 MI-related targets were obtained. In total, 126 core targets were screened according to topological analysis. KEGG results showed that RC was closely related to Phosphatidylinositol 3-kinase (PI3K)/Protein kinase B (PKB, also called Akt) signaling pathway. The experimental validation data showed that tetrahydropalmatine (THP) pretreatment preserved cell viability after OGD exposure. THP suppressed cardiomyocyte apoptosis and inflammation induced by OGD, while LY294002 blocked the inhibition effect of THP on OGD-induced H9c2 cells injury. Moreover, the molecular docking results indicated that THP had the strongest binding affinity with Akt rather than berberine, coptisine, palmatine and quercetin. Conclusions: THP, the active ingredient of RC, could suppress OGD-induced H9c2 cells injury though activating the PI3K/Akt pathway, which provides a scientific basis for novel strategy for MI therapy and RC application.